Os tutores na educação superior a distância: análise das dissertações e teses no portal Capes no período de 2006-2012 - Amaral, Sander de Sales (2013)
The process of expansion and democratization of higher education in the country, in recent decades, with the university reforms implemented by the State, has caused hard debate about the future of the university. It is in the midst of these reforms that the Distance Education (EaD) on upper level begins to expand, is viewed as strategic to democratize the access to higher education, by virtue of the possibilities arising from the improvement of Information Technology and Communication (TIC) from 1990s. Since then, their quality has been very questioned with the expansion of higher education by the distance education, where the problems of attendance and demand also are expanded, with implications on the academic teaching staff. And when we think of the expansion and quality in distance education, it is impossible not to give less importance to educational tutors, because the role and activity which are performed raise important issues for the development of our understanding on this non-presence education. Thus, our goal with this current study is to analyze the dissertations and theses into portal Capes surveyed in the period of 2006-2012 in order to understand how the authors situate the work of educational tutors in distance education who work in educational institutions linked to UAB, as regards to aspects such as professional identity, training, working conditions, among others. Therefore, we propose the following question: considering the analysis of dissertations and theses produced in portal Capes, the period of 2006-2012, what can we say about the tutors of EaD, understood as fundamental professionals to interact directly with students in the classroom poles and the virtual learning environment? In the methodology, we adopt two types of research: documents and literature. In documentary research, we analyzed documents written (laws, decrees, orders, notices, and other statistics), to verify the progress and prospects for the EaD in Brazil with the improvement of TIC. In the literature, apart from reading authors such as Castells, Schaff, Frigotto, Belloni, Barreto, Dourado, Santos, Toschi, Valente who have guided our study, we analyze theses and dissertations, selected in portal Capes, considering the period of 2006-2012. In the analysis developed , predominantly qualitative, we look at issues arising from the conceptions of the authors on the EaD, especially on aspects of the tutors‟ work , their specificities , their theoretical and methodological approaches , which enabled us to build a general framework in relation discussions on the subject. Analysis of State of the Art on studies involving tutors in distance education who work in education in IES members of UAB enables us to say that there are few dissertations and theses in the portal Capes on education tutors in IES members of UAB, many authors highlight the importance of tutors for the quality of distance education, so that some of them defend its function as teaching, but few roles deal about training and working conditions of these professionals, although, in some studies, it predominates discourse on the need for tutors and/or teachers in EaD with intent to adapt to technological advances, which is significant for the development of education, and know how to deal with the tools used in the process.